5(7-7x)=-35

Simple and best practice solution for 5(7-7x)=-35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(7-7x)=-35 equation:


Simplifying
5(7 + -7x) = -35
(7 * 5 + -7x * 5) = -35
(35 + -35x) = -35

Solving
35 + -35x = -35

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-35' to each side of the equation.
35 + -35 + -35x = -35 + -35

Combine like terms: 35 + -35 = 0
0 + -35x = -35 + -35
-35x = -35 + -35

Combine like terms: -35 + -35 = -70
-35x = -70

Divide each side by '-35'.
x = 2

Simplifying
x = 2

See similar equations:

| 5/x=11/7 | | 4x^2-14x+6*x-3= | | (x+8)(2x+14)=176+(x+15) | | 4x(y-7)=13 | | 4x(y+7)=13 | | 144=-6x+3xsquared | | ydx=x(1+xy^4)dy | | 10d+4=8d+6 | | (X*7)-(500+X)=(500-100) | | 8x-8=5x+6 | | 8n+15=4n+19 | | 7+3=1021 | | (x*7)-(500+X)=400 | | (x*7)-(500-X)=400 | | 4x^2-27x+16=-4x+1 | | 3x-2+5x=34 | | x^2+6x-9=2x+3 | | 2(2x-4)=39 | | x^2-10x+17=8 | | 7x+4x-x=60 | | v/9x=w/y | | 3(e-4)=2e | | 6x-3x=63 | | 5x+7-7x=29 | | [1,1,2][2,1,3][4,5,2]=[2,3,2] | | 7.35=2.45 | | 4m+3p-m-10p= | | 6x+3x=-63 | | -6x-3x=-63 | | 5(2z+5)=3(4z+3) | | 6x-11=5x+9 | | -5x+x=52 |

Equations solver categories